Dynamic and Static Modeling Embedded in Inquiry Learning to Improve Student’s Multiple Representation Ability - Langitasari, Indah; Effendy, Effendy; Fajaroh, Fauziatul (Jurnal Penelitian dan Pembelajaran IPA, 2018)
Integration of dynamic and static modeling on guided inquiry learning can help students to understand chemical concepts at macroscopic, symbolic and microscopic levels. This research aimed to examine and to explain the differences of students’ multiple representation ability that was taught by guided inquiry with dynamic and static modeling in redox reaction concept. This research used descriptive and quasi-experimental design. Data were analyzed using descriptive and manova statistics analysis. The results showed that the ability of students’ macroscopic level that was taught by guided inquiry with dynamic and static modeling is the same. While the student’s symbolic and microscopic level ability that was taught by guided inquiry with dynamic modeling higher than student’s ability that was taught by guided inquiry with static modeling. The implication of this research is chemistry learning with dynamic modeling can help students to construct chemical concept more easily and gain the complete understanding.